Structural insights into specificity and diversity in mechanisms of ubiquitin recognition by ubiquitin-binding domains. (21st March 2012) - Searle, Mark S.; Garner, Thomas P.; Strachan, Joanna; Long, Jed; Adlington, Jennifer; Cavey, James R.; Shaw, Barry; Layfield, Robert
Abstract : UBDs [Ub (ubiquitin)-binding domains], which are typically small protein motifs of <50 residues, are used by receptor proteins to transduce post-translational Ub modifications in a wide range of biological processes, including NF-κB (nuclear factor κB) signalling and proteasomal degradation pathways. More than 20 families of UBDs have now been characterized in structural detail and, although many recognize the canonical Ile 44 /Val 70 -binding patch on Ub, a smaller number have alternative Ub-recognition sites. The A20 Znf (A20-like zinc finger) of the ZNF216 protein is one of the latter and binds with high affinity to a polar site on Ub centred around Asp 58 /Gln 62 . ZNF216 shares some biological function with p62, with both linked to NF-κB signal activation and as shuttle proteins in proteasomal degradation pathways. The UBA domain (Ub-associated domain) of p62, although binding to Ub through the Ile 44 /Val 70 patch, is unique in forming a stable dimer that negatively regulates Ub recognition. We show that the A20 Znf and UBA domain are able to form a ternary complex through independent interactions with a single Ub molecule, supporting functional models for Ub as a 'hub' for mediating multi-protein complex assembly and for enhancing signalling specificity.